Is Gamification Effective for Women Who Wish to Learn Computer Programming? - Claudio Cubillos; Rafael Mellado; Cecilia Nóbile (Human Behavior and Emerging Technologies)
Women must be more represented in STEM careers, limiting their professional development opportunities. This study analyzes the effect of gamified software on women who want to learn computer programming. This experimental study investigated the effectiveness of gamification on programming learning in female college students. Thirty-two female students participated, randomly distributed into control (nongamified tools) and experimental (gamified tools) groups. The intervention lasted 4 weeks using Educaplay software, where the experimental group had access to a score and ranking as gamified elements. Learning outcomes, motivation, and usage levels were compared through pre- and posttests. There were no significant differences in learning between groups. In motivation, there were only differences in satisfaction, which were favorable to the group without gamification. There were no differences in usage, but the group without gamification scored higher in comfort. It is concluded that there is no solid evidence of the differential effectiveness of gamification for women to learn programming. It is necessary to consider gender stereotypes, motivational differences, and biases in design.